Number of fragments, margin status and thermal artifacts of conized specimens from LLETZ surgery to treat cervical intraepithelial neoplasia - Bittencourt, Dulcimary Dias; Zanine, Rita Maira; Sebastião, Ana Martins; Taha, Nabiha Saadi; Speck, Neila Góis; Ribalta, Julisa Chamorro Lascasas (São Paulo Medical Journal, 2012)
CONTEXT AND OBJECTIVE: Large loop excision of the transformation zone (LLETZ) is a nontraumatic cut and coagulation method with several advantages, but it induces thermal artifacts in the cut region. The aim here was to assess the correlations of age, number of fragments, lesion grade and degree of thermal artifacts with margin quality in conized specimens from LLETZ for cervical intraepithelial neoplasia (CIN). DESIGN AND SETTING: Cross-sectional study at Universidade Federal de São Paulo (Unifesp). METHODS: The records and histopathology findings of 118 women who underwent LLETZ between 1999 and 2007 were reviewed. Age, number of fragments, lesion grade, degree of thermal artifacts and margin quality were assessed. RESULTS: The patients’ mean age was 27.14 years; 63.6% had been diagnosed with CIN II and 36.4% with CIN III. The lesion was removed as a single fragment in 79.6% of the cases. The margins were free from intraepithelial neoplasia in 85.6% and compromised in the endocervical margin in 6.8%. Fragment damage due to artifacts occurred in 2.5%. Severe artifacts occurred in 22.8%. Women aged 30 years or over presented more cases of CIN III (P < 0.0004). Neoplastic compromising of surgical margins and severe artifacts occurred more often in cases in which two or more fragments were removed, and in patients aged 30 years or over. CONCLUSION: CIN III in women aged 30 or over, when removed in two or more fragments during LLETZ, presented a greater number of compromised margins and greater severity of thermal artifacts.